ANALISIS PUTUSAN HAKIM NOMOR: 113/Pid.B/2007/PN.Pml TENTANG TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Saryono Hanadi (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Decree Number: 113/Pid.B/2007/PN.Pml relating with the case of abuse of narcotic that conducted by Bambang Suroto alias Gentolet bin Rifa’i. In this case, public Prosecutor assert with laminated assertion which are Primer Assertion by article 81 sentence (1) letter a Law No.22 Year 1997 and subsidiary assertion by article 85 letter a Law No.22 Year 1997 concerning Narcotic. In this case, the decree cannot be told as a progressive decree because it not considering article 47 Law No. 12 Year 1997 concerning Narcotic. Judge ought to be considering the way to solve the problem by commanding the defendant to have the rehabilitation as a prevention without punishment to influencing views of society on crime.Keyword: abuse of narcotic, progressive decree and rehabilitation